Free Vibration of Simply Supported Beam on Elastic Foundations - Al-Azzawi, Adel A. (Al-Nahrain Journal for Engineering Sciences, 2017)
Fourier series and finite element analysis are utilized to obtain the solution of simply supported beams resting on elastic foundations with different loadings in order to arrive at a free vibration. The equation of the free vibration of beam on elastic foundation is derived and solved. Good agreement has been obtained between the results of the present study Fourier and finite element analysis and other previous solutions. The effect of modulus of subgrade reaction, axial tension force (foundation modulus) and beam depth on the behavior is studied.